The Role of Islamic Boarding Schools in Developing Student Leadership in Society - Marfiyanti Marfiyanti; Handriadi Handriadi; Eko Rojana; Zainal Arifin; Rahmad Hidayat; Defina Putri (STIT Ahlussunnah Bukittinggi, 2025)
This study aims to analyze the role of Islamic boarding schools in developing santri leadership in society. As Islamic educational institutions, pesantren not only function to teach religious knowledge, but also to shape the character and leadership spirit of santri. The research method used is qualitative with a case study approach, through literature analysis and observation of leadership practices in the pesantren environment. The results of the study show that Islamic boarding schools have two main roles in building student leadership. First, Islamic boarding schools serve as role models through the figures of kyai and ustadz who demonstrate leadership based on Islamic values. Second, Islamic boarding schools act as motivators by encouraging students to be active in organizational and social activities. The implications of this research confirm that Islamic boarding schools make an important contribution to producing a generation of leaders with noble character, integrity, and the ability to act as agents of change in society.